Body composition changes successfully classify prognosis in patients with mycobacterium avium complex lung disease. Issue 4 (October 2019) - Akahori, Daisuke; Suzuki, Yuzo; Yokomura, Koushi; Shirai, Masahiro; Yasui, Hideki; Hozumi, Hironao; Karayama, Masato; Furuhashi, Kazuki; Enomoto, Noriyuki; Fujisawa, Tomoyuki; Nakamura, Yutaro; Inui, Naoki; et al.
Highlights: Body composition changes were associated with worse survival in with MAC-LD. Especially, decreased ESMMA had prognostic values in patients with MAC-LD. Combined assessment of ESMMA and BMI accurately predicted the prognosis of MAC-LD. Summary: Objectives: Loss of body weight, a manifestation of cachexia, is frequently found in patients with Mycobacterium avium complex lung disease (MAC-LD) and known as a prognostic determinant. However, the involvement of body composition changes in the prognosis of patients with MAC-LD remains unclear. Methods: The cross-sectional-area of the erector spinea muscle (ESMCSA ) and mean attenuation of the erector spinae muscles (ESMMA ) in patients with MAC-LD, as determined by computed tomography imaging, were measured in two independent cohorts (137 and 111 patients, respectively). Results: Patients with MAC-LD showed significantly smaller ESMCSA together with lower body mass index (BMI), but no difference in ESMMA in both cohorts compared with controls. Smaller ESMCSA, body mass index decline, and decreased ESMMA were associated with worse survival in the patients. Among them, decreased ESMMA showed prognostic significance in the multivariate analyses. Importantly, assessment by ESMMA together with BMI successfully divided the patients into three groups with distinct prognoses. Conclusion: Changes in body composition, especially decreased ESMMA, had prognostic significance in patients with MAC-LD. Additionally, combined assessment of ESMMA and BMI accurately predicted the prognosis of MAC-LD, which may be a helpful tool for disease management. Graphical abstract: Image, graphical abstract